P-O05 Deconstructing Operations to Improve Recording of Surgical Training Experience. (16th December 2021) - Dewi, Ffion; Scroggie, Darren; Pathak, Samir; Blencowe, Natalie; Hollowood, Andrew; Strong, Sean; Jah, Asif; Smith, Andrew; Van Laarhoven, Stijn
Abstract: Background: A new outcomes-based curriculum is soon to be implemented for UK surgical trainees. Performance will be evaluated against the standard expected of a new consultant. Accurate recording of operative experience and performance will therefore be crucial to demonstrate achievement of this standard. The current eLogbook system for recording surgical experience has many benefits including simplicity and accessibility, but may misrepresent actual experience because most operations are considered as a whole; unlike some colorectal operations, involvement in steps within many upper gastrointestinal (UGI) operations cannot be recorded. Methods: Impact on training by the COVID-19 pandemic led to discussion and identification of cultural and logistical barriers to accurate recording of experience. To address these, a modification to enhance the current eLogbook system was developed by trainees and trainers at a university teaching hospital. An existing typology was used to deconstruct common UGI operations into their component steps, which can be recorded at this more detailed level. Results: The modified deconstructed logbook concept is described using a worked example, which can be applied to any operation. We also describe the integration of a component-based training discussion into the surgical team brief and debrief; this complements the deconstructed logbook by promoting a training culture. Conclusions: Using the described techniques, trainees of all levels can comprehensively and accurately describe their surgical experience. Senior trainees will benefit from recording complex operations which they are not expected to complete in their entirety, whilst less experienced trainees will benefit from the ability to record their involvement in more basic parts of operations. The suggested approach will reduce misrepresentation of experience, encourage proactive planning of training opportunities, and reduce the impact of crises such as pandemics on surgical training.